Debt And Equity-Based Financing, Size And Islamic Banks Profitability: Empirical Evidence From Indonesia - Rofiul Wahyudi; Siti Mujibatun; Riduwan Riduwan (Ekonomi Syariah IAIN Kudus, 2019)
Islamic Banking as a financial institution functions to collect and distribute funds to the public. To carry out these functions, the capital structure scheme uses debt and equity based financing. In addition, the implementation is also influenced by the size which ultimately affect the performance of Islamic banking. This study aims to examine debt and equity-based financing, size and Islamic banks profitability: empirical evidence from Indonesia. The research method used is model estimation test of Moderated Regression Analysis (MRA) to see size as moderation variable. Banks profitability is represented by ROA and ROE. This study uses Islamic bank panel data from financial reports published during the sample period covering 2008-2017. The empirical findings show that debt and equity-based financing affect banks profitability. Furthemore, bank size does not moderate the debt and equity-based financing relationship to Islamic banks profitability.